THE RELATIONSHIP BETWEEN KNOWLEDGE AND POVERTY: A Theoretical and Empirical Study in the Contemporary Era - Herawati; Supatmi; Werna Hendri Nopayana; Dadang; Koharudin; Sobirin (Journal of Education and Learning Sciences, 2026)
This study examines the relationship between knowledge and poverty from both theoretical and empirical perspectives in the contemporary era. Poverty is understood as a multidimensional phenomenon that extends beyond income deprivation to include limited access to education, healthcare, and social participation. Using a qualitative library research method, this study analyzes secondary data derived from academic journals, scholarly books, and reports from international institutions such as the World Bank, United Nations Development Programme, and International Labour Organization. The analysis employs a descriptive content analysis approach to synthesize findings from various sources. The results indicate that knowledge, particularly through education and digital literacy, plays a significant role in reducing poverty by increasing productivity, income, and access to economic opportunities. However, the relationship is not linear, as it is influenced by several mediating and moderating factors, including educational quality, labor market relevance, institutional capacity, access to financial capital, and structural inequalities. Furthermore, the study highlights the importance of digital literacy and gender equality as critical dimensions in contemporary poverty reduction efforts. This study concludes that knowledge can serve as a powerful instrument for poverty alleviation when supported by inclusive policies, relevant education systems, and equitable access to resources. Therefore, integrated strategies that combine educational improvement, digital inclusion, and institutional strengthening are essential to effectively address poverty in developing countries, including Indonesia.